2015
DOI: 10.1097/mnh.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta1 and aldosterone

Abstract: Purpose of review It is well established that blocking renin-angiotensin II-aldosterone system (RAAS) is effective for the treatment of cardiovascular and renal complications in hypertension and diabetes mellitus. Although the induction of transforming growth factor beta1 (TGFbeta1) by components of RAAS mediates the hypertrophic and fibrogenic changes in cardiovascular-renal complications, it is still controversial as to whether TGFbeta1 can be a target to prevent such complications. Here we review recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
1
8
0
1
Order By: Relevance
“…Transforming growth factor β (TGF‐β) is the best‐known fibrogenic growth factor during myocardial fibrosis . Studies show that TGF‐β signaling plays an important role in the regulation of the RAAS, matrix metalloproteinases (MMPs), inflammation, and immunity . A previous study showed that TGF‐β1 treatment significantly increased LOX expression in rat cardiac fibroblasts (RCFs), which could be prevented by inhibitors of PI3K, Smad3, p38‐MAPK, JNK, and ERK1/2 .…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor β (TGF‐β) is the best‐known fibrogenic growth factor during myocardial fibrosis . Studies show that TGF‐β signaling plays an important role in the regulation of the RAAS, matrix metalloproteinases (MMPs), inflammation, and immunity . A previous study showed that TGF‐β1 treatment significantly increased LOX expression in rat cardiac fibroblasts (RCFs), which could be prevented by inhibitors of PI3K, Smad3, p38‐MAPK, JNK, and ERK1/2 .…”
Section: Introductionmentioning
confidence: 99%
“…Protein TGF- β 1 is also involved in the RAAS process. In previous publications, it was reported that BP elevation may be promoted by TGF- β 1 through several mechanisms, such as stimulating endothelin mRNA expression in the vascular endothelium [ 21 ], suppressing renal tubular sodium reabsorption [ 22 ], and increasing renin release from juxtaglomerular cells in the kidney and AngII expression [ 23 ]. Besides, AngII also could induce time- and dose-dependent increases in TGF- β mRNA and activation, which directly results in excessive TGF- β [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Другой механизм заключается в воздействии альдостерона на систему фибринолиза. Доказано влияние гормона на ряд ингибиторов и активаторов плазминогена, в частности ингибитор активатора плазминогена 1-го типа (PAI-1) и тканевый активатор плазминогена (t-PA) [49,50]. Нарушение соотношения PAI-1/t-PA ведет к развитию дисбаланса системы фибринолиза и свертывающей системы.…”
Section: участие альдостерона в структурном ремоделировании предсердийunclassified